Pengembangan LKPD Berbasis Audio Visual dalam Pembelajaran Menulis Puisi di Kelas X SMA Al-Wasliyah Pasar Senen Medan - Kansal, Muhammad Faisal; Andriany, Liesna; Ali, Ali (Medan Resource Center, 2024)
This study endeavors to develop Audio Visual-based Student Worksheets (LKPD) for poetry writing material in class X at SMA Al-Washliyah Pasar Senen Medan. Employing the Research and Development (R&D) model, the study encompasses five steps: information gathering, product development, validation testing, product revision, and product testing. Data collection utilized a total sampling technique, testing 22 students in class X. Assessment percentages for the developed LKPD were: material validator one 77%, material validator two 79%, media validator one 95%, media validator two 84%, all judged proper. The student response questionnaire yielded an 84% score in the appropriate category. Analysis of poetry writing answer sheets revealed 17 students scoring above 75, with 5 below. Overall, results from the validator questionnaire test, feasibility questionnaire, and poetry writing analysis support the suitability of LKPD based on Audio Visual as an effective learning medium.